2014
DOI: 10.1063/1.4895385
|View full text |Cite
|
Sign up to set email alerts
|

Physical characterization of amorphous In-Ga-Zn-O thin-film transistors with direct-contact asymmetric graphene electrode

Abstract: High performance a-IGZO thin-film transistors (TFTs) are fabricated using an asymmetric graphene drain electrode structure. A-IGZO TFTs (channel length = 3 μm) were successfully demonstrated with a saturation field-effect mobility of 6.6 cm2/Vs without additional processes between the graphene and a-IGZO layer. The graphene/a-IGZO junction exhibits Schottky characteristics and the contact property is affected not only by the Schottky barrier but also by the parasitic resistance from the depletion region under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In this case, the large difference would have acted as a large potential barrier reducing the injection of electrons into the S/D contact region. 11,12) This would have led to a severe increase of parasitic resistance. Therefore, to apply graphene electrodes as S/D electrodes, it is essential to adopt argon plasma treatment before transferring the graphene electrode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the large difference would have acted as a large potential barrier reducing the injection of electrons into the S/D contact region. 11,12) This would have led to a severe increase of parasitic resistance. Therefore, to apply graphene electrodes as S/D electrodes, it is essential to adopt argon plasma treatment before transferring the graphene electrode.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that a-IGZO active layers and graphene electrodes show a large work function difference, leading to rectifying and blocking characteristics depending on the polarity of the drain-to-source voltage (V DS ) applied in the source/drain (S/D) electrode. 11,12) If V DS is applied in the forward direction, a-IGZO TFTs having asymmetric graphene electrodes show rectifying characteristics, while if V DS is applied in the reverse direction, they show blocking characteristics. In this case, if the graphene electrodes are applied as both S/D electrodes, the a-IGZO TFTs do not properly work because there is always a potential barrier in the S/D electrode regions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, charge focusing in the nanopatterned graphene strips provides greater changes in the Fermi level (changes that are quantitatively comparable to changes produced by chemical doping of graphene). While the emphasis in this work is on organic semiconductors, the hybrid channel nanoscale TFT geometry proposed here can also be advantageous for other classes of thin-film semiconductors including amorphous metal oxides , and two-dimensional (2D) semiconductors. In previous work, other approaches have been used to reduce contact resistance in organic TFTs, especially at the micrometer or tens of micrometer channel lengths. These include the use of polar self-assembled monolayer coatings on the metal electrodes to reduce the potential barrier between the metal Fermi level and the semiconductor conducing states. …”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that graphene/IGZO active layer which was fabricated on an opaque substrate exhibits Schottky diode behaviour due to the large difference in Fermi levels [5]. In this Letter, we fabricate a fully transparent a‐IGZO TFT and graphene/IGZO Schottky diode circuit.…”
Section: Introductionmentioning
confidence: 99%